Effectiveness of principals’ supervision and the learning performance of high school teachers through digital-based PLC - Hastuti, Rita; Johar, Permana; Taufani (Indonesian Research Journal in Education |IRJE|, 2025)
Teachers' learning performance can be improved through the principal's supervision by implementing several strategies and supporting tools. One of the strategies in learning supervision can be carried out through digital-based Professional Learning Communication (PLC) activities. The purpose of this study is to analyze the effectiveness of learning supervision in improving teacher learning performance through digital-based PLC activities, using a quantitative method with a multiple-regression research design. The results showed that the adjusted R2 (determination coefficient) was 0.934, meaning that the supervision activity of digital-based PLC (X1), and the supervision outcome activity of digital-based PLC (X2) contributed 93.4%, to the improving the learning performance of high school teachers (Y), while the remaining 6.6% explained by other factors that are not described in this study. The result of F (418.635) > F-table (3.91) and the significance value of P = 0.001 < α 0.05, means that the test model is feasible. In other words, there is a significant simultaneous influence of both variables on the improvement of high school teachers' learning performance (Y).